ANALISIS KEBUTUHAN RUANG PARKIR TERINTEGRASI UNTUK FIB, FH, DAN FISIP UNDIP KAMPUS TEMBALANG - Ferwira, Anda; Widihandoko, Andri; Purwanto, Djoko; Supriyono, Supriyono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Diponegoro University is a State University in Central Java. FIB, FH, and FISIP is part of some faculty at UNDIP. The layout of the three faculty are close each other. One of the problems from the three faculty is parking space requirements. Although it has provided a parking space (off street parking) in each faculty, but in reality there are many vehicles parked on the roadside (on street parking). This final report aims to evaluate the need of existing parking spaces and planned capacity expansion of existing parking spaces. Methodologies used include: field surveys, problem identification, data collection, test of the validity with chi-square test, data analysis, calculation of SRP needs, arrangement of the old park and planning of new park. The number of the current shortage of parking space requirements for overall three faculty is 91 SRP for cars and 59 SRP for motorcycles. Meanwhile for the development of the next 5 years is 138 SRP for cars and 466 SRP for motorcycles. Development of parking area with the integrated construction for FIB, FH, and FISIP are given alternative. Construction of the integrated parking building is planned 3 floors with total floor area of 5775 m². 1st floor with area of 1925 m² can serve 468 SRP motorcycles and 15 SRP cars. 2nd floor and 3rd floor with the same area is able to serve 62 SRP cars. Based on the analysis of the calculation, planning is considered to have been able to solve the needs of today and the parking spaces for the development of the next 5 years is until 2017. To solving the possibility of the occurrence of on-street parking, the solution is given by the installation of parking prohibition signs around the side of the road.